2019
DOI: 10.1186/s12889-019-7793-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementation strategy and cost of Mozambique’s HPV vaccine demonstration project

Abstract: BackgroundCost is an important determinant of health program implementation. In this study, we conducted a comprehensive evaluation of the implementation strategy of Mozambique’s school-based HPV vaccine demonstration project. We sought to estimate the total costs for the program, cost per fully immunized girl (FIG), and compute projections for the total cost of implementing a similar national level vaccination program.MethodsWe collected primary data through document review, participatory observation, and key… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The 15 studies included in our review were published between 2012 and 2020 and implemented across ten different countries (Mozambique, Zimbabwe, Peru, Uganda, Vietnam, Tanzania, New Zealand, USA, Belgium, and England). Five studies evaluated the cost of programs implemented in LMICs ( Alonso et al, 2019 , Hidle et al, 2018 , Levin et al, 2013 , Quentin et al, 2012 , Soi et al, 2019 ). One study conducted a CEA of a comprehensive vaccination program that also delivered HPV vaccines, and another study conducted a CEA of an ongoing national HPV vaccination program ( Blakely et al, 2014 , Wilson et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 15 studies included in our review were published between 2012 and 2020 and implemented across ten different countries (Mozambique, Zimbabwe, Peru, Uganda, Vietnam, Tanzania, New Zealand, USA, Belgium, and England). Five studies evaluated the cost of programs implemented in LMICs ( Alonso et al, 2019 , Hidle et al, 2018 , Levin et al, 2013 , Quentin et al, 2012 , Soi et al, 2019 ). One study conducted a CEA of a comprehensive vaccination program that also delivered HPV vaccines, and another study conducted a CEA of an ongoing national HPV vaccination program ( Blakely et al, 2014 , Wilson et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cost estimates to scale up a regional vaccination program in Tanzania were heavily impacted by salaries to international personnel and supervision, which accounted for more than 50% of vaccine delivery costs ( Quentin et al, 2012 ). There was a marked decrease in average startup costs from year one to year two of an implementation of a demonstration program in Mozambique that aimed at estimating projected costs of a national scale-up of an HPV vaccination program ( Soi et al, 2019 ). The greatest number of FIG 17,268 girls) resulted from the multi-regional study with an estimated financial and economic costs per FIG of US$ 5.71 and US$ 9.55 respectively, which were the lowest across all program cost evaluations ( Levin et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, the highest economic cost per dose at US$45.0 was in Zimbabwe and the lowest at US$3.09 was in Mwanza district in Tanzania, although the national average of US$10.62 for Tanzania may be a better comparison. Senegal had an economic cost of US$12.24 and financial cost of US$ 7.75, whereas Mozambique had an economic cost of US$24 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previous research has shown, a successful expansion of an HPV vaccination campaign to a national-level in a low-to-middle-income country requires local and international support and financial investment [24][25][26]. A key aspect highlighted by similar programs in Mozambique was that out-of-school and unenrolled girls would be missed by school-based vaccination programs; an adaptable model that would allow communities to target this demographic via both school-based and non-school based vaccination programs is recommended.…”
Section: Plos Onementioning
confidence: 99%